Modern Trends of Training Future Teachers of Physics to the Evaluation of Students' Educational Achievements - Andriy Levkovsky (Pedagogical Discourse, 2013)
The article highlights the current trends of training future teachers of physics to the monitoring and evaluation of educational achievements of schoolchildren. The examples of best practice assessment of the knowledge and skills of students. The basic principles of traditional systems of evaluation of educational achievements. The features of the rating system for evaluation of academic achievements of students in vocational and educational training of future teachers of physics are analyzed. The article identifies the benefits of using a rating system in comparison to existing methods of monitoring and evaluation of knowledge, skills and abilities. Further research evaluating the prospects of academic achievements of students are determined.